1
$\begingroup$

For

$\log_2(x) + 2\log_2(x-1) = 2 + \log_2(2x+1)$

I moved all the $x$ to left side, used got rid of log and got

$x-(x-1)^2 - (x+1) = 4$

Simplyifing I get

$x^2-2x=4$

The answer should be $x = 4$ (I checked on wolfram alpha) Help please?

$\endgroup$
  • $\begingroup$ Wellcome to MSE. If you make your question clear and show your trial, then you would obtain good feedback. Nice to meet you ! $\endgroup$ – HK Lee Oct 11 '14 at 3:53
0
$\begingroup$

Here are the steps I would use:

$\log_2(x) + 2\log_2(x-1) = 2 + \log_2(2x+1)$

$\log_2(x) + \log_2\left((x-1)^2\right) = \log_2\left(2^2\right) + \log_2(2x+1)$

That step turns each term into a base $2$ logarithm. Now they can be combined using the product rule for logs:

$\log_2\left(x(x-1)^2\right) = \log_2\left(4(2x+1)\right)$

Now you can get rid of the logarithms, and you get:

$x(x-1)^2 = 4(2x+1)$,

or

$x^3 - 2x^2 - 7x - 4 = 0$

This can be factored as $(x-4)(x + 1)^2=0$, which has solutions $x=4$ and $x=-1$. However, the second of these solutions is extraneous, which you can see by trying to plug it into the original equation.

Does that all makes sense?

$\endgroup$
  • $\begingroup$ Yes it makes sense. Thankyou! $\endgroup$ – Kieran Oct 11 '14 at 4:09
0
$\begingroup$

Using $\log a+\log b=\log(ab), m\log c=\log(c^m)$

We have $\log_2x(x-1)^2=\log_2(2^2)+\log_2(2x+1)=\log_24(2x+1)$

$\implies x(x-1)^2=4(2x+1)$

$\endgroup$
0
$\begingroup$

So many mistakes here. Your original intent seemed to be a good one. That should give

$$\log_2x+\log_2(x-1)-\log_2(2x+1)=2$$

What it looks like you did from here was to raise $2$ to the power of each term to get

$$x+(x-1)^2-(x+1)=4$$

It looks like you dropped the $2$ in the last log term and miscopied the problem here with a minus where you had a plus. In addition to that, the method is incorrect. You must use the properties $\log a+\log b=\log ab$ or $n^{a+b}=n^an^b$. It's probably best to use properties of logarithms to combine everything on the left into a single logarithm. This results in

$$\log_2\dfrac{x(x-1)^2}{2x+1}=2$$ $$\dfrac{x(x-1)^2}{2x+1}=4$$ $$x^3-2x^2+x=8x+4$$ $$x^3-2x^2-7x-4=0$$ $$(x-4)(x+1)^2=0$$

Since the log of a negative number is undefined, the only solution that works is $x=4$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.